1993
DOI: 10.1111/1523-1747.ep12363290
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Channel Conductance as a Control Mechanism in Hair Follicles.

Abstract: The opening of intracellular potassium channels is a common mechanism of action for a set of anti-hypertensive drugs that includes the hair-growth-inducing agent minoxidil. Recent work suggests potassium channel openers (PCOs) also influence hair growth. Correlative studies demonstrate that a series of PCOs including minoxidil, pinacidil, P-1075, an active pinacidil analog, RP-49,356, cromakalim, and nicorandil maintain hair growth in cultured vibrissa follicles. Studies using balding stumptail macaques verify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…50 Another randomized, placebo controlled trial comparing the efficacy of topical 5% solution with topical 2% and placebo in women Table I. Minoxidil: proposed mechanisms of action Vasodilatory properties 16,38 Angiogenic properties 17 Enhanced cell proliferation and DNA synthesis 24,27 Potassium channel opener 39,40 Antiandrogen effects 41 Suppression of collagen synthesis 42,43 Immunosuppressive effects 32,35,36 demonstrated statistically significant increased hair growth in both the 5% and 2% group over the placebo group, but not necessarily in the 5% over the 2% group. 51 There was an increased occurrence of pruritus, irritation, and hypertrichosis in the 5% versus the 2% group.…”
Section: Minoxidil For Androgenetic Alopeciamentioning
confidence: 99%
“…50 Another randomized, placebo controlled trial comparing the efficacy of topical 5% solution with topical 2% and placebo in women Table I. Minoxidil: proposed mechanisms of action Vasodilatory properties 16,38 Angiogenic properties 17 Enhanced cell proliferation and DNA synthesis 24,27 Potassium channel opener 39,40 Antiandrogen effects 41 Suppression of collagen synthesis 42,43 Immunosuppressive effects 32,35,36 demonstrated statistically significant increased hair growth in both the 5% and 2% group over the placebo group, but not necessarily in the 5% over the 2% group. 51 There was an increased occurrence of pruritus, irritation, and hypertrichosis in the 5% versus the 2% group.…”
Section: Minoxidil For Androgenetic Alopeciamentioning
confidence: 99%
“…In addition, streptomycin was included in the vibrissae study and only increased cysteine incorporation was measured, which may not equate to greater hair length. Finally, the concentration of the drugs used differed; although the glibenclamide concentrations are similar, Buhl et al (1993) used a minoxidil concentration 100-fold higher and lower tolbutamide concentrations.…”
Section: Figurementioning
confidence: 99%
“…There is growing evidence that K + channels may serve functions necessary for cell proliferation [33,39], and specific openers of inwardly rectifying Kir6/SUR (K ATP ) channels (pinacidil, minoxidil and cromakalim) are used clinically to stimulate hair growth in patients with alopecia [2,5]. Recently, it has been shown that these K ATP channel openers increase the mitogen-induced proliferation and DNA synthesis of liver cells [21].…”
Section: Introductionmentioning
confidence: 99%